2008
DOI: 10.1002/glia.20683
|View full text |Cite
|
Sign up to set email alerts
|

Activated microglia modulate astroglial enzymes involved in oxidative and inflammatory stress and increase the resistance of astrocytes to oxidative stress in Vitro

Abstract: Neuropathological processes in the central nervous system are commonly accompanied by an activation of microglia and astrocytes. The involvement of both cell populations in the onset and progress of neurological disorders has been widely documented, implicating both beneficial and detrimental influences on the neural tissue. Nevertheless, little is known about the interplay of these glial cell populations, especially under diseased conditions. To examine the effects of activated microglia on astrocytes purifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 88 publications
2
29
1
Order By: Relevance
“…It is possible that after the 10gf + chr injury, the actions of reactive microglia, such as production and release of nitric oxide and phagocytosis, induce astrocytic reactivity, and that the application of sTNFR1 may be ineffective in reducing these aspects of microglial reactivity. 37 A study of nerve transection showed no effect of either sTNFR1 or IL-1ra or a combination of the two treatments on microglial reactivity in the spinal cord. 49 Although microglia contain cytokine receptors and respond to pro-inflammatory cytokines, those cells are sensitive to a wide range of insults and a pharmacologic block of pro-inflammatory cytokines may not necessarily modulate other signaling molecules that induce reactivity in microglia.…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that after the 10gf + chr injury, the actions of reactive microglia, such as production and release of nitric oxide and phagocytosis, induce astrocytic reactivity, and that the application of sTNFR1 may be ineffective in reducing these aspects of microglial reactivity. 37 A study of nerve transection showed no effect of either sTNFR1 or IL-1ra or a combination of the two treatments on microglial reactivity in the spinal cord. 49 Although microglia contain cytokine receptors and respond to pro-inflammatory cytokines, those cells are sensitive to a wide range of insults and a pharmacologic block of pro-inflammatory cytokines may not necessarily modulate other signaling molecules that induce reactivity in microglia.…”
Section: Discussionmentioning
confidence: 98%
“…Up to now, the many direct consequences of a primary stimulation of astrocytes have been characterized in great detail (5,27,69). The next logical step toward an understanding of chronic neuroinflammation and the multiple activation states cells can take is the study of the reactions of astrocytes in different preactivation states.…”
Section: Discussionmentioning
confidence: 99%
“…The next logical step toward an understanding of chronic neuroinflammation and the multiple activation states cells can take is the study of the reactions of astrocytes in different preactivation states. Large phenotypic alterations are suggested by the few existing studies showing an increased resistance to oxidative stress, altered CD95 signaling, or an altered inflammatory modulation by adenosine (4,59,69). However, much more work will be required to examine whether prestimulated astrocytes show different pharmacological properties or whether their response to endogenous damage signals is altered.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of members of different GSTs in astrocytes is likely to be regulated separately. At least a treatment of astrocytes with conditioned media from activated microglial cells increased the expression of GSTpi1 and GST-mu3, while treatment with conditioned media from non-activated microglial cells only increased GSTpi1 but decreased GST-mu3 expression [141]. As another trigger ethyl pyruvate was identified to elevate GST levels in primary astrocytes via activation of Nrf2 [48].…”
Section: Conjugation Of Gsh With Endogenous Compounds and Xenobioticsmentioning
confidence: 99%